2007
DOI: 10.1016/j.reprotox.2006.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Induction of mammary gland ductal hyperplasias and carcinoma in situ following fetal bisphenol A exposure

Abstract: Exposure of the fetus to excess estrogen is believed to increase the risk of developing breast cancer during adult life. Fetal exposure to low doses of the xenoestrogen bisphenol A resulted in long-lasting effects in the mouse mammary gland that were manifested during adult life. It enhanced sensitivity to estradiol, decreased apoptosis, increased the number of progesterone receptor-positive epithelial cells at puberty and increased lateral branching at 4 months of age. We now report that fetal exposure to 2.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
227
2
8

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 286 publications
(249 citation statements)
references
References 57 publications
12
227
2
8
Order By: Relevance
“…27 Although the treatment dose of 400 µg kg –1 BW day –1 was high, the mean concentration of unconjugated BPA in maternal serum was 0.68 ng mL –1 , similar to what is measured in humans 98. A study in Wistar‐Furth rats revealed that fetal exposure to BPA (2.5, 25, 250, 1000 µg kg –1 BW day –1 ) via an implanted osmotic pump resulted in a 3–4 fold increase in the number of hyperplastic ducts at postnatal day (PND) 50 at all doses, and led to a significantly elevated number of these structures at PND90 at only the lowest dose 25. BPA was also found to increase the incidence of mammary tumors in Sprague Dawley rats treated with a range of BPA (0.25, 2.5, 25, 250 µg kg –1 BW day –1 ) during gestation or during both gestation and lactation 26.…”
Section: Epidemiological Animal and In Vitro Evidence Of Bpa‐associsupporting
confidence: 65%
See 2 more Smart Citations
“…27 Although the treatment dose of 400 µg kg –1 BW day –1 was high, the mean concentration of unconjugated BPA in maternal serum was 0.68 ng mL –1 , similar to what is measured in humans 98. A study in Wistar‐Furth rats revealed that fetal exposure to BPA (2.5, 25, 250, 1000 µg kg –1 BW day –1 ) via an implanted osmotic pump resulted in a 3–4 fold increase in the number of hyperplastic ducts at postnatal day (PND) 50 at all doses, and led to a significantly elevated number of these structures at PND90 at only the lowest dose 25. BPA was also found to increase the incidence of mammary tumors in Sprague Dawley rats treated with a range of BPA (0.25, 2.5, 25, 250 µg kg –1 BW day –1 ) during gestation or during both gestation and lactation 26.…”
Section: Epidemiological Animal and In Vitro Evidence Of Bpa‐associsupporting
confidence: 65%
“…Estrogenic responses, including enhanced uterine wet weight, increased luminal epithelial cell height within the uterus, and induced lactoferrin expression, were observed in immature female mice treated with BPA 130. An increase in mammary epithelial cell proliferation was also observed in animals exposed to low doses of BPA, indicating an estrogenic response of the mammary glands to BPA 25, 104…”
Section: Mechanisms Underlying Bpa‐stimulated Carcinogenic Effectsmentioning
confidence: 94%
See 1 more Smart Citation
“…proliferating) and ER-positive compared to controls at PND 50 (Murray et al, 2007). Surprisingly, at PND 90, only those animals exposed to the lowest dose of BPA had a significant increase in the number of these structures compared with controls while animals exposed to the two highest doses developed severe dysplastic changes (Murray et al, 2007). Invasive cancers were observed in those animals exposed to low doses of BPA when they were further challenged by a sub-carcinogenic dose of the chemical carcinogen N-nitroso-N-methylurea at puberty (Durando et al, 2007).…”
Section: Bisphenol a (Bpa)mentioning
confidence: 97%
“…Experiments on Wistar-Furth rats exposed to low concentrations of BPA from embryonic day 9 through postnatal day (PND) 1 (2.5, 25, 250, or 1,000 µg BPA/kg body weight/day), showed that rats exposed to any of the above BPA doses had a 3-to 4-fold increase in the number of hyperplastic ducts that were Ki67-positive (i.e. proliferating) and ER-positive compared to controls at PND 50 (Murray et al, 2007). Surprisingly, at PND 90, only those animals exposed to the lowest dose of BPA had a significant increase in the number of these structures compared with controls while animals exposed to the two highest doses developed severe dysplastic changes (Murray et al, 2007).…”
Section: Bisphenol a (Bpa)mentioning
confidence: 99%